2021
DOI: 10.1111/clr.13706
|View full text |Cite
|
Sign up to set email alerts
|

Implant soft tissue Dehiscence coverage Esthetic Score (IDES): A pilot within‐ and between‐rater analysis of consistency in objective and subjective scores

Abstract: Objectives To introduce an esthetic index for assessing the outcomes of peri‐implant soft tissue dehiscence/deficiency (PSTD) coverage and test its within‐ and between‐reviewer reliability. Materials and Methods Photographs of 51 single PSTDs at baseline and after treatment were provided to four periodontists from three centers. The examiners were asked to rate each case at two timepoints with the Implant soft tissue Dehiscence/deficiency coverage Esthetic Score (IDES) that involved the evaluation of the post‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Considering this rise and popularity in dental implant treatment, it is crucial to acknowledge and study the complications that may accompany these procedures. These can include the onset of peri‐implant diseases that can eventually lead to the loss of the implant itself, 3–7 or esthetic challenges in the presence of implant health such as the occurrence of peri‐implant soft tissue dehiscence/deficiencies 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…Considering this rise and popularity in dental implant treatment, it is crucial to acknowledge and study the complications that may accompany these procedures. These can include the onset of peri‐implant diseases that can eventually lead to the loss of the implant itself, 3–7 or esthetic challenges in the presence of implant health such as the occurrence of peri‐implant soft tissue dehiscence/deficiencies 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…When focusing on esthetics evaluation, Zucchelli et al (2018) and Roccuzzo et al (2019) obtained at the 5‐year follow‐up good results and reported high patients´ satisfaction, but a comparison is difficult to make because both studies (Roccuzzo et al, 2019; Zucchelli et al, 2018) used a different evaluation scale VAS vs. pink and white esthetics score (PES/WES) (Belser et al, 2009; Fürhauser et al, 2005). For comparable and unified esthetic evaluation of BSTD coverage, Zucchelli et al (2021) developed the implant soft tissue dehiscence coverage Esthetic Score (IDES). The IDES involved four clinical variables: post‐treatment level of the soft tissue margin, peri‐implant papillae height, mucosa color, and mucosa appearance.…”
Section: Discussionmentioning
confidence: 99%
“…For comparable and unified esthetic evaluation of BSTD coverage,Zucchelli et al (2021) developed the implant soft tissue dehiscence coverage Esthetic Score (IDES). The IDES involved four clinical variables: post-treatment level of the soft tissue margin, peri-implant papillae height, mucosa color, and mucosa appearance.IDES seems to be a good approach for the standardized evaluation of esthetic assessments following BSTD coverage of implantsupported single crowns bounded by two natural teeth and would allow comparison of the esthetic outcome of different BSTD augmentation procedures.The acquisition of long-term data and the control of peri-implant health with tailored supportive periodontal therapy (STP) requires the measurement of clinical parameters during the follow-up period.Both studies(Zucchelli et al, 2013 andRoccuzzo et al, 2014) documented the progression of clinical parameters and were able to show a significant increase in CAL, KT (Zucchelli et al, 2013), and PPD TA B L E 3 Secondary outcomes Study Significant differences and correlations of secondary outcome(s) Burkhardt et al () STT: positive relation between the flap thickness and mean percentage of coverage of BSTD Anderson et al (2014) test group Wound healing more adverse with an ADM Increase of mucosal phenotype (p < .001) Mucosal phenotype correlated negatively with the distance from the crown to the gingival margin (p < .05) → the longer the crown, the thinner the phenotype Anderson et al (2014)…”
mentioning
confidence: 99%
“…In addition, among studies, different reference points to evaluate the peri-implant recession, as well as various indices for the assessment of the aesthetic outcome, have been used. Therefore, direct comparison of the clinical results is not always easy or meaningful [8,12]. In order to overcome this problem in future studies, Zucchelli et al introduced a new Implant soft tissue Dehiscence coverage Esthetic Score (IDES) for a more objective evaluation of the treatment outcome that incorporates and standardizes both clinical and aesthetics outcomes, as mentioned above [8].…”
Section: Surgical Techniques For the Treatment Of Pstdmentioning
confidence: 99%
“…The facial contour and the level of the soft tissue margin are significant variables of these indices [5][6][7]. Recently, Zucchelli et al introduced a new index (IDES) specifically for PSTD, in which the evaluation begins at least six months after the surgical attempts for coverage [8]. Specifically, four parameters are evaluated, which are the level of the soft tissue margin (STM), the peri-implant papillae height (PPH) compared with the homologous tooth, the peri-implant mucosa color, and the peri-implant mucosa appearance (PMA).…”
Section: Introductionmentioning
confidence: 99%